Respiratory, cardio-metabolic and neurodevelopmental long-term outcomes of moderate to late preterm birth: not just a near term-population. A follow-up study - Alonso-Lopez, Patricia; Arroyas, Maria; Beato, Maite; Ruiz-Gonzalez, Sara; Olabarrieta, Iciar; Garcia-Garcia, Maria Luz (Frontiers in Medicine, 2024)
Introduction Moderate-to-late preterm infants constitute the majority within the preterm infant population. Most research on preterm infants has focused on very preterm children, often treating moderate-to-late preterm infants as similar to full-term infants. Our objective was to compare clinical, respiratory, cardio-metabolic and neurodevelopmental outcomes in adolescents aged 12–15 years born moderate and late preterm with a control group of the same age born full-term. Methods Observational cross-sectional study, comparing moderate-to-late preterm (32–36+6 weeks’ gestational age) with full-term adolescents (37–41+6 weeks’ gestational age; 75 each group). Perinatal and neonatal history were collected as well as data on respiratory evolution (ISAAC questionnaire for asthma symptoms for adolescents 13–14 years), anthropometric values, learning difficulties, behavioral test (screening questionnaire for high-performance autism spectrum disorder and evaluation test for attention deficit hyperactivity disorder), skin prick test, pulmonary function test, echocardiogram and blood pressure. A blood test with metabolic profile was conducted. Results Moderate-to-late preterm adolescents had more current asthma [p = 0.008, OR3 (95% CI 1.26–7.14)] and longer duration of combined treatments to control asthma (inhaled corticosteroids and anti-leukotrienes; p = 0.048). Forced vital capacity <80% was detected more often in moderate-to-late preterm patients (p = 0.013). When assessing right ventricle, moderate-to-late preterm adolescents showed better tricuspid annular plane systolic excursion z-score (p = 0.003), shortening fraction (p < 0.001) and E/A ratio z-score (p = 0.002). Regarding left ventricular assessment, moderate-to-late preterm group had smaller ventricle diastolic diameter (p = 0.04) and lower posterior wall z-score values (p = 0.037). They also showed a better S’wave z-score (p = 0.027), E wave (p = 0.005), E/A ratio (p = 0.003) and a higher septal myocardial performance index z-score (p = 0.025). Moderate-to-late preterm adolescents presented lower weight z-score (p = 0.039), body mass index z-score (p = 0.013), Waterlow weight index (p = 0.006) and higher undernutrition index [p = 0.04; OR 1.4 (95% CI 1–1.9)]. Although there were no differences in neurodevelopmental survey or behavioral tests. Conclusion Our findings underscore the importance of extended follow-up for this predominant group of premature infants to identify potential respiratory, cardiac and anthropometric issues that may emerge in the future.